Improvement of Life Period of Biofertilizers by Addition of Humic Acid and Flyash - Jayanthi, C. (Asian Journal of Chemistry, 2010)
The aim of this work is to improve the storage life and quality of biofertilizers namely azospirilum, rhizobium and phosphobacteria by the inclusion of 1 % humic acid and 1 % flyash. The physico-chemical values, electrical conductivity, pH, percentage of carbon, organic matter, bulk density and water holding capacity of humic acid and flyash were determined. Then, the storage life and quality of the biofertilizers were tested in usual packing, packing with 1 % humic acid, packing with 1 % flyash and packing with both 1 % humic acid 1 % flyash of these biofertilizers for 5 months at 15, 30, 45, 60, 90, 120 and 150 d intervals. It was concluded that the inclusion of both 1 % humic acid and 1 % fly ash with usual packing of biofertilizers increased the life period of biofertilizers.